Irkutsk Renaissance in wood - Zolotareva, Milena; Eremin, Nikita (project baikal, 2026)
Almost thirty years ago, the only monument of Vladimir Pavlov’s wooden architecture was destroyed in a fire. It is unique in its realization, but programmatic in its creative endeavor. The House of Fisherman and Hunter embodied an unprecedented idea of connecting the spirit of material and place with the reinterpretation of traditional technology in the pure functional aesthetics of the author’s technique. Thanks to timely photofixation and preserved sketches, the research and design team of the Department of History and Theory of Architecture of St. Petersburg State University of Architecture and Civil Engineering managed to develop a method of sequential reconstruction that allows us to accurately recreate this timeless example of modern architecture.
Keywords: architect V. A. Pavlov; House of Fisherman and Hunter; residence “Angarsk Farms”; Taltsy Architectural and Ethnographic Museum